Real-world data from the use of ranolazine in patients with stable angina pectoris: the RANGER study. (3rd October 2022) - Stafylas, P; Olympios, C; Dermitzakis, A; Efthimiadis, I; Gardikiotis, A; Kakouros, S; Lampropoulos, S; Barbetseas, J; Sourgounis, A
Abstract: Background: Although ranolazine is available since years as a second-line treatment to reduce angina attacks in patients with stable angina pectoris, real-world data on effectiveness, tolerability and safety of ranolazine are limited. Methods: A non-interventional, prospective study conducted to assess the effectiveness and safety of ranolazine. Patients eligible for enrolment had a baseline assessment between one and fourteen days after initiating ranolazine for the first time and a follow-up visit three months later. Primary endpoints comprised the weekly frequency of angina attacks, total adverse events and ranolazine discontinuation rate. Secondary endpoints included the use of short-acting nitrates, changes on the Canadian Cardiovascular Society (CCS) angina classification score and quality of life scale score (QoL). Results: In total, 1, 101 patients were enrolled in 214 sites. Mean weekly angina attacks were reduced from 3.6±2.9 to 0.4±0.9 (p<0.0001) and the mean weekly consumption of short-acting nitrates decreased by 1.7±2.2 (p<0.0001). CCS class and QoL were also improved (p<0.0001). Adverse events were reported by 11 (1%) patients totally, while 2 of them (0.2%) were characterized as serious. Treatment was discontinued for any reason in 23 patients (2.1%) after the follow-up period. Ranolazine treatment was equally effective in all subgroups tested, with larger benefits observed in patients with more frequent angina and CCS angina class III and IV. Up-titration of ranolazine during the study improved the outcomes. Conclusion: Ranolazine was well-tolerated and effectively reduced angina attacks with simultaneous improvement of CCS class and QoL score in patients with stable angina. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): The study was sponsored by Menarini Hellas. The study sponsor was involved in the study concept and design and in the interpretation of the data included in this publication, but not in the data collection and analysis. Menarini Hellas also funded the medical writing support for this publication.